Proceedings of Offshore Technology Conference 2010
DOI: 10.2523/20617-ms
|View full text |Cite
|
Sign up to set email alerts
|

High-Viscosity Oil-Gas Flow in Vertical Pipe

Abstract: The objectives of this study are to collect data of high-viscosity oil-gas flow in upward vertical pipe and assess the performance of existing mechanistic models developed based on low viscosity liquid experimental results. In this study, oil with viscosity between 0.1 and 0.5 Pa·s (100 and 500 cP) corresponding to temperatures from 37.8 to 15.6 °C (100 to 60 °F) and natural gas at 2.515 MPa (350 psig) pressure are used as the two phases. Superficial oil velocity lies in the range from 0.1 to 1.0 m/s and super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…At low gas flow rate, liquid film falls downward and is picked up by the upcoming slug. This phenomenon is the reason that causes positive frictional pressure gradient, which is against ordinary expectation but is confirmed in the current experiments and previous Akhiyarov et al (2010) experimental study.…”
Section: Fig 7: Horizontal Stratified Gas-liquid Flow With Oil In Wasupporting
confidence: 82%
See 2 more Smart Citations
“…At low gas flow rate, liquid film falls downward and is picked up by the upcoming slug. This phenomenon is the reason that causes positive frictional pressure gradient, which is against ordinary expectation but is confirmed in the current experiments and previous Akhiyarov et al (2010) experimental study.…”
Section: Fig 7: Horizontal Stratified Gas-liquid Flow With Oil In Wasupporting
confidence: 82%
“…This system was previously used by Vuong (2009), Akhiyarov (2010 and Sridhar (2011). This facility consists of three main systemsoil, water and gas systems, and three auxiliary systems -instrumentation air, glycol temperature control and data acquisition systems.…”
Section: Multiphase Flow Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include in this study the limited number of reports for downward concurrent gas-liquid flows in vertical pipes (Barnea et al, 1982;Julia et al, 2013;Kim et al, 2004) because conditions that draw gas bubbles or slugs down with liquid flows are less common in industrial applications than upward flow conditions. Although most of the co-current upward flow studies used air with water, eight studies report co-current experiments in vertical pipes with hydrocarbon liquids or glycerol-water solutions (Akhiyarov et al, 2010;Alruhaimani, 2015;Da Hlaing et al, 2007;Furukawa & Fukano, 2001;Oddie et al, 2003;Omebere-Iyari et al, 2007;Schmidt et al, 2008;Szalinski et al, 2010). Three studies report experiments with nitrogen gas instead of air (Oddie et al, 2003;Omebere-Iyari et al, 2007;Schmidt et al, 2008).…”
Section: Co-current Upward Flow In Vertical Pipesmentioning
confidence: 99%
“…In another study Schmidt et al(2008) investigated the effect of liquid viscosity on upward vertical gas-liquid flows in a tube with 54.5 mm inner diameter and mixtures of nitrogen and solutions of polyvinylpyrrolidone in water with dynamic viscosities in the range of 900-7000 mPa s. They observed a decrease in the gas holdup with increasing the liquid viscosity from 1 to 480 mPa s. They also compared the flow map for liquid viscosity of 1600 mPa s with the air-water flow map of and concluded that the transition to annular regime occurred at lower gas superficial velocities in the viscous liquid. Akhiyarov et al (2010) conducted experiments on gas-oil flows in vertical pipes with internal diameter of 52.5 mm and oil viscosities of 100-500 mPa s to assess the performance of the available mechanistic models to predict the pressure gradient and liquid holdup. No comparison was reported on the effect of liquid viscosity on the liquid holdup and flow regimes.…”
Section: Effect Of Pipe Deviationmentioning
confidence: 99%